Characterisation of phenolic compounds in wild fruits from Northeastern Portugal - Guimarães, Rafaela (2013)
This study aimed to analyse the phenolic composition of wild fruits of Arbutus unedo (strawberry-tree), Prunus spinosa (blackthorn), Rosa canina and Rosa micrantha (wild roses). Analyses were performed by HPLC-DAD-ESI/MS. P spinosa fruits presented the highest concentration in phenolic acids (29.78 mg/100 g dry weight), being 3-O-caffeoylquinic acid the most abundant one, and flavone/ols (57.48 mg/100 g), among which quercetin3-O-rutinoside (15.63 mg/100 g) was the majority compound. (+)-Catechin was the most abundant compound in A. unedo (13.51 mg/100 g) and R. canina (3.59 mg/100 g) fruits. A. unedo fruits presented the highest concentration in flavan-3-ols (36.30 mg/100 g). Cyanidin 3-O-glucoside was found in all the studied fruits, being the major anthocyanin in most of them, with the exception of P. spinosa samples, in which cyaniding 3-O-rutinoside and peonidin 3-O-rutinoside predominated; P. spinosa fruit presented the more complex anthocyanin profile among the analysed fruits and also the highest anthocyanin concentrations, which was coherent with its greater pigmentation. All in all, P. spinosa presented the highest levels of phenolic acids and flavonoids, including anthocyanins, flavonols and flavones, although no flavan-3-ols could be identified in its fruits. The present study represents a contribution to the chemical characterisation of phenolic compounds from wild fruits with acknowledged antioxidant activity and traditionally used for several folk medicinal applications.